Permasalahan Komunikasi Yang Kerap Terjadi Pada Penyandang Disabilitas - Adam Nurmansyah; Nanda Rizqia Rhamadhani; Sabrina Alfarissy Nur Hakim; Sri Azhari Agustin; Siti Hamidah (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
The background of this research is to understand how to communicate with persons with disabilities. The purpose of this research is for the general public to understand how to interact properly and correctly with persons with disabilities. The research method used in this study is a qualitative description method. The results of this study were to obtain data on communication problems that often occur between people with disabilities and how to communicate well with people with disabilities. The conclusion of this study is that it is difficult for people with disabilities to communicate, the right way to communicate is to communicate with love and feelings and with soft words.